2021
DOI: 10.1164/rccm.202004-1132oc
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine Receptor 2–targeted Molecular Imaging in Pulmonary Fibrosis. A Clinical Trial

Abstract: Idiopathic pulmonary fibrosis (IPF) is a progressive, inflammatory lung disease that is monitored clinically by measures of lung function, without effective molecular markers of disease activity or therapeutic efficacy. Lung immune cells active in the pro-fibrotic process include inflammatory monocyte and interstitial macrophages that express the C-C motif chemokine receptor 2 (CCR2). CCR2 + monocyte lung influx is essential for disease phenotypes in models of fibrosis and identified in lungs from subjects wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 64 publications
2
51
0
Order By: Relevance
“…A signi cant anti-in ammatory activity of NINT was noted only on WBC in BALF; on the contrary, only a mild and non-signi cant inhibition was observed in the M2-like population by FACS. Although the pivotal role of macrophages in IPF has been recently well reported 31,32 , the modulatory effect of NINT on macrophage polarization in vivo has been only demonstrated in Fra2 transgenic mice, ameliorating histological features of pulmonary arterial hypertension 33 . In human macrophages, NINT treatment was able to downregulate M2 markers of expression in vitro 34 .…”
Section: Discussionmentioning
confidence: 99%
“…A signi cant anti-in ammatory activity of NINT was noted only on WBC in BALF; on the contrary, only a mild and non-signi cant inhibition was observed in the M2-like population by FACS. Although the pivotal role of macrophages in IPF has been recently well reported 31,32 , the modulatory effect of NINT on macrophage polarization in vivo has been only demonstrated in Fra2 transgenic mice, ameliorating histological features of pulmonary arterial hypertension 33 . In human macrophages, NINT treatment was able to downregulate M2 markers of expression in vitro 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Single cell preparations were analyzed by mass cytometry as previously described 51 . Briefly, cells were labeled using a previously validated and titrated antibody cocktail for surface markers 51 (all antibodies conjugated by the manufacturer-Fluidigm) diluted in Fluidigm MaxPar Cell Staining Buffer (CSB) (1 hour at 4 °C). After two washes in CSB, cells were fixed in 2% PFA for 20 min at room temperature, washed, stained with MaxPar Intercalator-IR (Fluidigm) and filtered into cell strainer cap tubes.…”
Section: Methodsmentioning
confidence: 99%
“…The authors later compared 68 Ga-to 64 Culabelled ECL1i in cardiac injury and found comparable radiotracer uptake in the ischemic area [101]. Recently, the group also reported proof-of-concept for 64 Cu-DOTA-ECL1i PET in the detection of abdominal aortic aneurysm (AAA) [36] and pulmonary fibrosis [37] in rodent models and human tissue. Remarkably, 64 Cu-DOTA-ECL1i uptake was twice as high in AAA that subsequently ruptured compared to non-ruptured AAA.…”
Section: C-c Motif Chemokine Receptor 2 (Ccr2)mentioning
confidence: 99%
“…Mainly expressed on pro-inflammatory monocytes, natural killer cells and T cells Lung inflammation [34], cardiac injury [35], abdominal aortic aneurysm [36], pulmonary fibrosis [37] Promising [38], atherosclerosis [39], vascular inflammation [40,41], rheumatoid arthritis [42][43][44]…”
Section: Expressed On Several Pro-inflammatory Immune Cells Particularly Overexpressed On Macrophages and T Cellsmentioning
confidence: 99%